Effect of dietary energy source on pregnancy rates and reproductive physiology of pastured beef heifers - Davis, Ty C.; Amirault, Katherine E.; Stewart, Jacob W.; Gleason, Claire B.; Dias, Nicholas W.; Timlin, Claire L.; Seekford, Zachary K.; Ealy, Alan D.; Mercadante, Vitor R. G.; White, Robin R. (Frontiers in Animal Science, 2023)
Proper production of steroid hormones, such as progesterone (P4), is essential for maintenance of pregnancy. Provision of gluconeogenic substrates from the diet may alter postabsorptive energy supplies and associated hormone signaling in a manner supportive of elevating P4 concentrations. Crossbred Angus heifers (n=27) were balanced for pre-trial bodyweight (BW) and body condition score (BCS), then assigned to isoenergetic diets leveraging starch (ES) or fat (EF) as the primary source of energy (45.7% starch vs 11.5% fat). The heifers were placed on the assigned diets 8 days prior to the initiation of estrous synchronization and continued the diets through the second pregnancy diagnosis, 52 days after the initial insemination. On day 28 post-breeding, pregnancy status was diagnosed via ultrasonography. Measurements of follicle size and number were collected via rectal palpation and ultrasonography on days −10, −8, −4, and day 0 relative to breeding. Blood samples were collected on days −10, 1 through 7, 10, 14, 18, 21, 24, and 28 to analyze plasma for P4 concentrations and placental-associated glycoprotein (PAG) concentrations. Data were analyzed using a linear mixed effects model with a fixed effect for treatment and a random effect for pen. Observations collected over time were analyzed using a repeated measures approach with fixed effects for treatment, time, initial condition, and a random effect for pen. Interactions between treatment and pregnancy status were also tested for PAG and P4 concentrations. No treatment differences were observed in final BCS (P=0.12) and total dry matter intake (DMI; P=0.51), though heifers on the ES treatment tended to reach an increased BW (P=0.10). Although heifers fed ES diets had numerically higher conception rates compared to heifers fed EF diets (71.4% vs. 66.7%), there was no statistically significant difference. Furthermore, there were no significant differences observed among diets in terms of pregnancy outcomes, follicle size, or number. A treatment by pregnancy status interaction was detected for both PAG and P4 concentrations. These results suggest that short-term dietary starch supplementation provided around the time of breeding can result in shifts to reproductive hormone abundance that may be conducive for pregnancy establishment.